Herbal Medicines in the Management of Diabetes: Ethnobotanical Insights and Pharmacological Perspectives - V.Roopa,; S.Mahalakshmi,; K.Prithisha,; S.Nivetha,; R.Gokul,; Dr.S.Anbazhagan,; K. Reeta Vijayarani,; S.A.Vadivel, (Asian Journal of Pharmaceutical Research and Development, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia due to defects in insulin secretion, insulin action, or both. Despite the availability of synthetic antidiabetic drugs, their long-term use is often associated with adverse effects and limited efficacy in managing complications. In recent decades, there has been a growing interest in the use of herbal medicines as complementary or alternative therapeutic options for diabetes management. This review provides comprehensive ethnobotanical insights into medicinal plants traditionally used across different cultures for their antidiabetic potential. It highlights key herbal species, their traditional uses, and the phytoconstituents responsible for glycemic control. Furthermore, the review discusses the pharmacological mechanisms underlying their antidiabetic activities, including insulin mimetic effects, β-cell protection, inhibition of carbohydrate-hydrolyzing enzymes, and antioxidant actions. Several plant-derived compounds such as flavonoids, alkaloids, saponins, and terpenoids have shown promising results in preclinical studies. By integrating ethnobotanical knowledge with pharmacological evidence, this review underscores the potential of herbal medicines as effective and safer alternatives for diabetes management and encourages further research and clinical validation.